Computed tomography of the chest in patients with COVID-19: what do radiologists want to know? - Razek, Ahmed (Pol J Radiol, 2021)
We aim in the current study to review pulmonary and extra-pulmonary imaging features in patients infected with COVID-19. COVID-19 appears to be a highly contagious viral disease that attacks the respiratory system causing pneumonia. Since the beginning of the outbreak, several reports have been published describing various radiological patterns related to COVID-19. Radiological features of COVID-19 are classified into; pulmonary signs of which ground glass opacities are considered the characteristic followed by consolidation, and extra-pulmonary signs such as pulmonary embolism and pneumothorax, which are far less common and appear later in progressive disease. We review the different structured reporting systems that are published by different groups of radiologists using simple unified terms to enable good communication between the radiologist and the referring physician. Computed tomography of the chest is beneficial for early diagnosis of COVID-19 pneumonia, assessment of disease progression and guide to therapy, surveillance of patients with response to therapy, prediction of overlying bacterial infection, differentiation from simulating lesions, and screening with prevention and controls of the disease.